2020
DOI: 10.3390/app10144736
|View full text |Cite
|
Sign up to set email alerts
|

Studies of Buried Layers and Interfaces of Tungsten Carbide Coatings on the MWCNT Surface by XPS and NEXAFS Spectroscopy

Abstract: Currently, X-ray photoelectron spectroscopy (XPS) is widely used to characterize the nanostructured material surface. The ability to determine the atom distribution and chemical state with depth without the sample destruction is important for studying the internal structure of the coating layer several nanometers thick, and makes XPS the preferable tool for the non-destructive testing of nanostructured systems. In this work, ultra-soft X-ray spectroscopy methods are used to study hidden layers and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 85 publications
1
11
0
Order By: Relevance
“…At the same time, there are significant differences in the spectrum of the nanocomposite: a 2.1-fold decrease in the area under the spectral curve, the appearance of an additional structure with three low-intensity peaks, A, B, C, and a shoulder D in the region between the π* and σ* resonances. The energy positions of the additional peaks are in good agreement with the energies of the C1s → π* transitions in the C-O (A, 286.9 eV), C-O-C (B, 287.7 eV), (C, 288.6 eV, as part of the carboxy and carbonyl group), and CO 3 (D, 290.4 eV) groups, which is confirmed by the numerous studies of carbon oxides [12,14,33,42] and various oxygen-carbon containing molecular groups [34,[43][44][45][46]. However, in [47], it is noted that the C 1s → π* electron transition in the carboxy-COOH group C=O coupling lies in the 290.0-290.4 eV range, although other authors associate this transition with the absorption band at a photon energy of 288.6 eV [34,42,44,45].…”
Section: Nexafs and Xps Study Of Cu/mwcntssupporting
confidence: 83%
See 3 more Smart Citations
“…At the same time, there are significant differences in the spectrum of the nanocomposite: a 2.1-fold decrease in the area under the spectral curve, the appearance of an additional structure with three low-intensity peaks, A, B, C, and a shoulder D in the region between the π* and σ* resonances. The energy positions of the additional peaks are in good agreement with the energies of the C1s → π* transitions in the C-O (A, 286.9 eV), C-O-C (B, 287.7 eV), (C, 288.6 eV, as part of the carboxy and carbonyl group), and CO 3 (D, 290.4 eV) groups, which is confirmed by the numerous studies of carbon oxides [12,14,33,42] and various oxygen-carbon containing molecular groups [34,[43][44][45][46]. However, in [47], it is noted that the C 1s → π* electron transition in the carboxy-COOH group C=O coupling lies in the 290.0-290.4 eV range, although other authors associate this transition with the absorption band at a photon energy of 288.6 eV [34,42,44,45].…”
Section: Nexafs and Xps Study Of Cu/mwcntssupporting
confidence: 83%
“…It is also suggested [20] that the shoulder D at 290.4 eV in the C 1s NEXAFS spectrum of CuO/graphene reflects the presence of the strong bonding between the Cu 2 O and graphene sheet by forming a Cu-O-C bond. In our previous studies [12,14], the D band was also observed in the C 1s NEXAFS spectra of the Cr/MWCNTs, Fe/MWCNTs, and WC/MWCNTs nanocomposites. Therefore, the appearance of the D band should be associated with the formation of compounds containing anion CO 3 2− during the nanocomposite synthesis.…”
Section: Nexafs and Xps Study Of Cu/mwcntsmentioning
confidence: 74%
See 2 more Smart Citations
“…The near edge X-ray absorption fine structure (NEXAFS) spectroscopy [26] and X-ray photoelectron spectroscopy (XPS) [27,28] are effective experimental methods that allow us to directly obtain detailed information about the nanoscale atomic-electron structure of the polyatomic system under study. Their combination with traditional Raman spectroscopy and X-ray diffractometry (XRD) provides new reliable knowledge about the atomic and electronic structure of nanostructured carbon materials [29,30]. In this work, the successive modification of fullerite C 60, as a result of HIP at a pressure of 0.1 GPa in an argon atmosphere in the temperature range of 920-1270 K, was characterized by XRD, XPS, NEXAFS and Raman spectroscopy.…”
Section: Introductionmentioning
confidence: 99%